2019
DOI: 10.31703/grr.2019(iv-iii).56
|View full text |Cite
|
Sign up to set email alerts
|

Investigating ESL Learners' Motivation through ARCS Motivational Design Model

Abstract: This research aimed to determine whether there exists a relationship between the four elements of Keller's ARCS motivation framework and undergraduate students' motivation to learn English as a second language. ARCS' is the acronym for Attention, Relevance, Confidence and Satisfaction. This study employed a quantitative approach and used a survey questionnaire for collecting data from 300 students enrolled in the undergraduate programs in four universities (two public sectors and two private sectors). The ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The findings of this study also suggested that there are strong correlations between learning strategies and every motivation component in the ARCS model. These results are in line with the study by Javed et al (2019) on student motivation for learning English as a second language (ESL).…”
Section: Conclusion 51 Summary Of Findings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of this study also suggested that there are strong correlations between learning strategies and every motivation component in the ARCS model. These results are in line with the study by Javed et al (2019) on student motivation for learning English as a second language (ESL).…”
Section: Conclusion 51 Summary Of Findings and Discussionsupporting
confidence: 91%
“…According to Gonen and Akbarov (2016) and Wan Daud et al (2020), the ARCS model's Satisfaction element has the greatest mean compared to attention, relevance, and confidence. Javed et al (2019) found a positive correlation between all four ARCS model factors and students' willingness to learn, while Chang et al (2016) found that M-IBL students with motivational enhancement had significantly higher learning motivation than those without MSs in ARCS relevance, confidence, and satisfaction but no significant difference in Attention.…”
Section: Past Studies On the Use Of Learning Strategies And Arcs Moti...mentioning
confidence: 95%
“…Loorbach et al (2015) conducted a study in a self-directed learning environment and concluded that a reduced version of IMMS, called RIIMS (Reduced Instructional Materials Motivation Survey) fitted the four factors of the ARCS model with an instrument that consisted of 12 items. In the framework of languages to see if undergraduate students' are motivated to learn English as a second language (Javed et al, 2019).…”
Section: Arcs Model Of Motivational Designmentioning
confidence: 99%